PENGARUH STRUKTUR AKTIVA, PROFITABILITAS DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN INDUSTRI PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Andini Nurwulandari (GoAcademica Research dan Publishing, 2020)
This study aims to determine the effect of asset structure, profitability and liquidity on the capital structure of mining industry companies listed on the Indonesia Stock Exchange (IDX). This study uses quantitative methods with data sources in the form of company financial statements compiled and published online by the Indonesia Stock Exchange (IDX), and library studies. The analysis was performed using descriptive statistical analysis, multiple linear regression and bivariate correlation test. The results showed that the asset structure had a positive effect on the capital structure, meaning that the more complex the asset structure, the more complex the capital structure was. On the other hand, profitability and liquidity variables have no effect on capital structure.